Diet of Arctic Foxes (Alopex lagopus) in Greenland - Kapel, Christian M.O. (ARCTIC, 1999)
The gastrointestinal tracts of 254 arctic foxes (Alopex lagopus) trapped or shot in Greenland, mainly during winter, were examined for the presence of food items. The occurrence of different food categories in the gastrointestinal tracts differed significantly between the geographical areas. Overall frequencies of occurrence of food categories were the following: berries (0-67%), seaweed (0-50%), other plant material (6-57%), bird and bird eggs (0-83%), fish (0-31%), shellfish (0-33%), reindeer (0-29%), sheep (0-25%), seal (0-12%), insects (0-10%), larger pieces of muscle tissue (12-57%), human food waste (0-77%), and nonfood garbage (0-50%). In foxes caught near air bases, the gastointestinal tracts were frequently (53-70%) found to contain human food waste and nonfood garbage. Foxes caught in the more remote districts of Greenland seem less dependent on waste and garbage; they feed on a broad variety of food items according to the local diversity of the prey fauna. On a examiné le tube digestif de 254 renards arctiques (Alopex lagopus) piégés ou abattus au Groenland, surtout durant l'hiver, en vue d'étudier la présence des différents aliments. L'occurrence de diverses catégories de nourriture dans les tubes digestifs variait largement selon les aires géographiques. Dans l'ensemble, la fréquence de l'occurrence des catégories d'aliments était la suivante: baies (0-67 p. cent), algues marines (0-50 p. cent), autres éléments végétaux (6-57 p. cent), oiseaux et oeufs d'oiseaux (0-83 p. cent), poisson (0-31 p. cent), crustacés et coquillages (0-33 p. cent), renne (0-29 p. cent), mouton (0-25 p. cent), phoque (0-12 p. cent), insectes (0-10 p. cent), gros morceaux de tissu musculaire (12-57 p. cent), déchets de cuisine (0-77 p. cent) et déchets non alimentaires (0-50 p. cent). On a trouvé que chez les renards capturés près des bases aériennes, le tube digestif contenait souvent (53-70 p. cent) des déchets de cuisine et des déchets non alimentaires. Les renards capturés dans les régions plus reculées du Groenland ...